Anthropometry-driven block setting improves starting block performance in sprinters - Cavedon, V.; Sandri, M.; Pirlo, M.; Petrone, N.; Zancanaro, C.; Milanese, C. (PLOS ONE, 2018)
This study tested the effect of two block setting conditions i.e., the usual block setting [US] and an anthropometry-driven block setting [AS] on the kinematic and kinetic parameters of the sprint start. Furthermore, we verified whether this effect is influenced by the relative lengths of the sprinter`s trunk and lower limbs i.e., the Cormic Index by subdividing sprinters into brachycormic, metricormic and macrocormic groups. Forty-two sprinters performed 6 maximal-effort 10 m sprints using the US and AS conditions. Dynamometric starting blocks measured forces generated by the sprinters. The times at 5 m and 10 m in the sprint trials were measured with photocells. Results showed that the anteroposterior block distances were significantly different between the two conditions (P<0.001). Across the sample, the horizontal block velocity, the rear peak force, the rear force impulse, the total force impulse, the horizontal block power, the ratio of horizontal to resultant impulse in the rear block, the first and second step lengths and the times at 5 m and 10 m improved in AS vs. US (P values from 0.05 to 0.001). Considering the interaction between the block setting condition and the Cormic Index, the rear peak force and the rear force impulse were significantly increased in the metricormic and brachycormic groups (P=0.001) and the metricormic group (P<0.001), respectively. Kinetic variables in the rear block and the difference (Delta) in the front block/starting line distance between US and AS were related with each other (Adjusted R2 values from 0.07 to 0.36). In conclusion, AS was associated with improvement in the kinematic and kinetic parameters of the sprint start performance vs. US; however, AS is apparently best suited for metricormic sprinters. Further work is needed to verify how the sprint start kinetic and kinematic parameters are related to the front block/starting line distance and whether a block setting driven by the sprinter`s Cormic Index is able to improve sprint start performance.